Educational and moral values in children's theatre-The play The Skilled Hunter by Izz al-Din Jalawji is a model (مجلة إحالات, 2026)
Children's theater is one of the most important means of education, as it plays a role It is important in instilling educational and moral values in the hearts of children. Therefore,this research paper will introduce children’s theater and its most important features, with a focus on the most important educational and moral values contained in “The SkilledFisherman’s Play.”Through which the writer tried to provide a set of advice and instructions that benefit children in particular, it is also loaded with a set of educational values that contribute toraising the child in a sound upbringing. In this play, an easy language was adopted that suits this age group.